MATURATION OF MACROPHAGES UNDER THE INFLUENCE OF MURAMYL PEPTIDES - A. Il’inskaya; L. Pichugina; N. Oliferuk; V. L’vov; B. Pinegin (Медицинская иммунология)
Abstract. Muramyl peptides from bacterial cell wall trigger the modifications in macrophages similar to maturation observed with dendritic cells. Mature macrophages reduced their capacity for phagocytosis, comparing with control, while the bactericidal activity increased. Phenotype analysis of human macrophages exposed to muramyl peptides showed the increasing expression of costimulatory receptors and antigen presenting molecules. On the other hand, there was downregulation of receptors involved in recognition and engulfing of microorganism. In response to bacterial component macrophages secreted several cytokines: IL–12, TNFα, IL–6. (Med. Immunol., 2005, vol.7, № 1, pp. 21526)